Edukasi Manajemen Pola Diet pada Pasien Diabetes Mellitus Tipe II - Jundapri, Kipa; Suharto, Suharto; Olivia, Nina; Bagaskara, Gustaf Wijang (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2025)
Diabetes Mellitus is a condition of hyperglycemia because of the abnormalities in insulin secretion or insulin action. Diet pattern will provide benefits for the quality of life of diabetes mellituss’ patients. The service activity was carried out in March 2023 with 3 stages consisting of 30 respondents with 3 stages: stage 1  data collection, blood sugar checking before education, stage 2 providing education and stage 3 or post-test stage (after education was carried out), there was an increase in knowledge before it was given education was 30%, and after the education was given it became 90%, and there was a decrease in blood sugar levels from before the education was given, 250 mg/dL after the education was given to 220 mg/dL.